Examining Teachers’ Perceived Barriers to the Integration of Critical Thinking in Moroccan High Schools - Youssouf Laabidi (ASIAN TEFL Journal of Language Teaching and Applied Linguistics, 2019)
Several scholars acknowledge that the ability to think critically and process new information is a skill that must be learnt in order to challenge a rapidly changing world. It is important to enhance students’ critical thinking skills to help them be successful in their upcoming life plans in numerous domains. In other words, integrating critical thinking skills in schools is not only a way to assist learners obtain favorable outcome in schools, but it is also crucial if learners are going to be able to operate in an increasingly difficult world. However ; little attention has been given to examine strategies that can help teachers incorporate critical thinking skills in education. This paper attempts to address the importance of critical thinking in education. Besides, it aims to discuss the issue of teaching critical thinking for the 21st century students learning English as a foreign language. Finally, the paper  addresses elements that prevent the improvement of critical thinking in classrooms.